Prevalence of attention deficit hyperactivity disorder symptoms among primary school children in Nigeria: a comparison of teachers and parent reports - Hogan, Ekemini; Akpan, Mkpouto; Ijezie, Echey; Edem, Kevin (International Journal of Research in Medical Sciences, 2022)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most common neuro-behavioral disorders of childhood.Though ADHD is the most extensively studied neuro-behavioral disorder in childhood, its prevalence rate has not been documented in our environment. Aim of the current study was to determine the prevalence and subtypes of ADHD among primary school pupils living in Ikot-Ekpene, a semi-urban area in Nigeria’s rainforest. Methods: This was a cross-sectional study conducted among 1174 primary school pupils aged 6-12 years selected from twelve primary schools in Ikot Ekpene local government area of Akwa Ibom state. The Vanderbilt rating scale for both teachers and parents were administered by teachers and parents of the pupils and the prevalence rate of ADHD was determined. Results: One hundred and forty-six pupils met the rating scale criteria for probable ADHD using the teacher’s scale with a prevalence of 12.4%, while 8.5% met the criteria using the parent’s scale. Of the three different subtypes of ADHD, the hyperactive subtype was the most prevalent subtype on both the teacher’s and parent’s scales (52.7% and 46% respectively). The inattentive subtype was 32.9% and 33.0% on the teachers and parents scale respectively. The combined subtype was the least prevalent on both scales. Conclusions: Prevalence rate of ADHD in children is significant in our environment. Policies should be put in place to implement the screening test for ADHD under the school health program for the early identification of pupils with ADHD.